2000
DOI: 10.1046/j.1365-2141.2000.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the cellular immune response after autologous peripheral blood stem cell transplantation in patients with non‐Hodgkin's lymphoma

Abstract: Peripheral blood stem cell (PBSC) transplants may be depleted of lymphoid progenitors, thereby disabling the cellular immune response against viral pathogens after autologous PBSC transplantation (PBSCT). To monitor the cellular immune reconstitution after autologous PBSCT, we investigated the cytolytic activity (CLA) of peripheral blood T lymphocytes against Epstein-Barr virus (EBV) in 13 patients with non-Hodgkin's lymphoma or multiple myeloma. The individual EBV-directed CLA (EBV-CLA) was determined by calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Mya et al demonstrated that HBV reactivated at 3-5 months post-transplant (26). Interestingly, based on immune reconstitution reports on patients treated with ASCT, this is the time of recovery of cellular immunity after ASCT (27)(28)(29). In our series, 12 patients with HBV reactivation, reactivation occurred within 6 months of HDT/ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…Mya et al demonstrated that HBV reactivated at 3-5 months post-transplant (26). Interestingly, based on immune reconstitution reports on patients treated with ASCT, this is the time of recovery of cellular immunity after ASCT (27)(28)(29). In our series, 12 patients with HBV reactivation, reactivation occurred within 6 months of HDT/ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…To test the approach of TCR genetic engineering of HSCs in the clinic, we designed a clinical trial of double cell therapy coadministering HSCs and T cells both genetically modified to express an NY-ESO-1 TCR. We propose to use 2 TCR-engineered cell therapies because we anticipate that the TCR-engineered HSCs will endogenously differentiate into fully active mature T cells with a long delay in their appearance in the periphery, as new T cells reaching peripheral circulation must undergo a thymic selection process which takes 1 to 3 months (20,21). In this clinical trial, TCR-engineered mature lymphocytes and TCRengineered HSCs will be coadministered to patients with NY-ESO-1-positive advanced cancers after a myelo-and lymphodepleting conditioning regimen.…”
Section: Introductionmentioning
confidence: 99%